2017
DOI: 10.1038/s41559-017-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

Induced defences in plants reduce herbivory by increasing cannibalism

Abstract: Plants are attacked by myriad herbivores, and many plants exhibit anti-herbivore defences. We tested the hypothesis that induced defences benefit tomato plants by encouraging insects to eat other members of their species. We found that defences that promote cannibalism benefit tomatoes in two ways: cannibalism directly reduces herbivore abundance, and cannibals eat significantly less plant material. This previously unknown means of defence may alter plant-herbivore dynamics, plant evolution and pathogen transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…A growing body of work provides convergent evidence that infants and young children are sensitive to ancestrally-recurrent naturalistic threats. For example, children as young as three years of age more quickly detect the presence of snakes and spiders compared to control stimuli (LoBue & DeLoache, 2008;LoBue, 2010a); an advantage that persists into adulthood (New & German, 2015;Öhman, Flykt, & Esteves, 2001). Similar results have been found with infants.…”
Section: Responses To Ancestrally-recurrent Threats In Infancy and Eamentioning
confidence: 99%
“…A growing body of work provides convergent evidence that infants and young children are sensitive to ancestrally-recurrent naturalistic threats. For example, children as young as three years of age more quickly detect the presence of snakes and spiders compared to control stimuli (LoBue & DeLoache, 2008;LoBue, 2010a); an advantage that persists into adulthood (New & German, 2015;Öhman, Flykt, & Esteves, 2001). Similar results have been found with infants.…”
Section: Responses To Ancestrally-recurrent Threats In Infancy and Eamentioning
confidence: 99%
“…The induction of plant defenses can increase cannibalism rates (Orrock et al. ), which, according to theory, may either increase (Sadeh and Rosenheim ) or decrease transmission (Van Allen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that induction of plant defenses can change cannibalism rates (Orrock et al. ) and can affect disease transmission (Sadeh and Rosenheim , Van Allen et al. ), these two processes may well interact to influence transmission in systems where they both arise.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of insect herbivores, one possibility lies in exploiting the tendency of these predators to fall back on cannibalism when the plants on which they are feeding are either consumed, lose nutritional value or otherwise become harder to eat. A recent study showed that, under controlled conditions, it is possible to induce cannibalism among caterpillar predators ( Spodoptera exigua ) by triggering the jasmonic acid pathway . This stimulates production of various chemicals, including phenolic molecules that reduce palatability, such as flavonoids, isoflavonoids, anthocyanins and lignins.…”
Section: Hormone‐controlled Networkmentioning
confidence: 99%